ISLAM AND THE FAILURE OF MODERNIZATION IN THE MIDDLE EAST - Ahmad Sahide (Al-Albab, 2012)
This paper tries to see the encounter between Islam and modernity in the countries where the majority of the inhabitants are Muslims, particularly in the Middle East that is currently in the state of turmoil. In General, modernity failed to adapt to the Islamic states, for example the failure of democracy, which became the current joint attention in some Arab countries where the iron fist regimes are still a part of the political system. Furthermore, this paper attempts to see why modernity is difficult to adapt itself in the Middle East which began to build relations with Europe in the 18th century. Bernard Lewis, an expert who focuses on the Islamic world, argued that the failure of modernity in the Middle East and Islamic countries because of cultural factors and understanding of religion that hampered the pace of modernity. The understanding of religion is still centered on debating the democratic system and gender equality which come from the West; all of which is part of modernity. In addition, the young generations that learn a lot from the West, are not given broader space to apply their knowledge in developing and setting up a system of nationhood and statehood. These are the core issues that will be discussed further in this paper. Keywords: Modernity, Middle East tensions, and Islam